Analysis of Quality of Antibiotic Usage on Patient with Internal and Surgical Service - Ma'rifah, Nurul; Hasmono, Didik; Hadi, Usman; Kuntaman, Kuntaman (Folia Medica Indonesiana, 2021)
It is well-known that hospitals are health facility with the widely use of antibiotics. It is about 13-37% from the total hospitalized patients in developed countries use antibiotic, even in developing countries can reach 30-80%. There is identified correlation between antibiotic use and the development of bacterial resistance. Even though the resistance cannot be eliminated, but its development can be suppressed by the increasing of prudent use of antibiotics. The aim of this study was to determine the quality of antibiotic use on internal medicine and surgical patients in Aisiyah Hospital Bojonegoro. The study was a prospective cross sectional observational analytical study of among patients of internal and surgical who received antibiotic therapy in the period of August - September 2017. The total 50 samples were collected in this study which consists of 33 internal medicine and 17 surgical patients. From 50 samples, there were 16 types of antibiotics with the total use of 81 of antibiotic use. As the result, in internal medicine patients there were 22 (40%) of appropriate use of antibiotics, 4 (7.27%) of inappropriate use and 29 (52.73%) use of antibiotics without indication. In surgical patients, there were 12 (46.15%) of appropriate use of antibiotics, 2 (7.69%) of inappropriate use and 12 (46.15%) use of antibiotics without indication. This study showed that more than 50% of antibiotic use were inappropriate, and mainly antibiotic with no indication, among patients hospitalized in Aisyiyah Hospital Bojonegoro.